1999
DOI: 10.1039/a907565h
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular co-ordination networks constructed via pi-stacking interactions and charge-assisted hydrogen bonds

Abstract: The diprotic acid 3,4-dihydroxy-3-cyclobutene-1,2-dione (squaric acid, H 2 SQA) reacts with [(η 5 -C 5 H 5 ) 2 Co] in THF to form a hydrogen bonded co-ordination network in crystalline {[Co II (HSQA-HSQA) 2 (H 2 O) 4 ] 2-}{[(η 5 -C 5 H 5 ) 2 Co III ] + } 2 (1) which contains Co II and Co III metal centres and the supramolecular salt {[(η 5 -C 5 H 5 ) 2 Co III ] + }{[(HSQA)(H 2 SQA)] -} (2) depending on the solvent and on the stoichiometric ratio. The diprotic acid pyridine-2,6-dicarboxylic acid (dipicolinic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…3 and 4. The squarate monoanion dimer is rare, and we have found only eight examples in the CSD (Angelova et al, 1996;Bernardinelli et al, 1989;Bock et al, 1998;Braga et al, 1999;Braga & Grepioni, 1998;Kanters et al, 1991;Karle et al, 1996;MacLean et al, 1999). In all other squarate structures, the squarate monoanions are linked by a single intermolecular OÐHÁ Á ÁO hydrogen bond and no tenmembered rings are formed.…”
Section: Figurementioning
confidence: 83%
See 1 more Smart Citation
“…3 and 4. The squarate monoanion dimer is rare, and we have found only eight examples in the CSD (Angelova et al, 1996;Bernardinelli et al, 1989;Bock et al, 1998;Braga et al, 1999;Braga & Grepioni, 1998;Kanters et al, 1991;Karle et al, 1996;MacLean et al, 1999). In all other squarate structures, the squarate monoanions are linked by a single intermolecular OÐHÁ Á ÁO hydrogen bond and no tenmembered rings are formed.…”
Section: Figurementioning
confidence: 83%
“…Squaric acid (3,4-dihydroxy-3-cyclobutene-1,2-dione) is a very strong dibasic acid and has been studied for potential application to xerographic photoreceptors, organic solar cells and optical recording (Seitz & Imming, 1992;Liebeskind et al, 1993). From the viewpoint of crystal engineering, squaric acid is also a useful tool for constructing crystalline architectures, because of its rigid and¯at four-membered ring framework, and its proton donating and accepting capabilities for hydrogen bonding (Braga et al, 1999;Reetz et al, 1994). We have recently shown that the simple combination of chloranilic acid and various dipyridyl-type ligands can create a variety of supramolecular architectures involving an in®nite one-dimensional molecular tape structure (Zaman et al, 1999(Zaman et al, , 2000.…”
Section: Commentmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] The first [Cr(dipic) 2 ] − complex containing inorganic cationic counter ion, has been NH 4 [Cr(dipic) 2 ].…”
Section: Complex Anion [Cr(dipic) 2 ]mentioning
confidence: 99%
“…hydrogen bonding, ionic interactions and π-π stacking interactions have fascinated increasing attention in crystal engineering. In particular, hydrogen bonding π-π stacking interactions which is a powerful organizing force in designing various supramolecular and solid-state architectures [8][9][10], is extensively used not only for networking numerous organic and organometallic compounds [11,12], but also for generating interesting supramolecular properties, such as electrical, optical and magnetic [13,14] properties. Quinoline groups, with effective sites for coordination to transition metal ions, have been used for the construction of supramolecular coordination compounds [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%